Evaluation of the Effect of Different Ferrule Designs on Fracture Resistance of Maxillary Incisors Restored with Bonded Posts and Cores - Z. Mahdavi Izadi; E. Jalalian; A. Eyvaz Ziaee; L. Zamani; B. Javanshir (Tehran University of Medical Sciences, 2010)
Introduction: In cases of severe hard tissue loss, 2 mm circumferential ferrule is difficult to achieve. So in these cases we should use different ferrule designs. This in vitro study investigated the effect of different ferrule designs on the fracture resistance of teeth restored with bonded post and cores. Materials and Methods: Forty freshly-extracted central incisors were endodontically treated. The teeth were randomly divided into four groups; group 1 were teeth with 2 mm circumferential ferrule above the CEJ, group 2 were teeth with 2 mm ferrule only on the palatal side of the teeth, group 3 consisted of teeth with 2 mm ferrule only on the facial side and group 4 were teeth with 2 mm ferrule on the palatal and facial side of teeth with interproximal concavities. All teeth were restored with fiber posts and composite cores. The specimen was mounted on a universal testing machine and compressive load was applied to the long axis of the specimen until failure occurred. Results: The fracture resistance was 533.79 ± 232.28 in group 1, 634.75± 133.35 in group 2, 828.90 ±118.27 in group 3 and 678.78± 160.20 in group 4. The post hoc analysis showed statistically significant difference between groups 1 and 3 . Conclusions: The results of this in vitro study showed that facial ferrule increases the fracture resistance of endodontically treated teeth restored with bonded post and cores.